Frequency and temperature dependent electrochemical characteristics of carbon-based electrodes made of commercialized activated carbon, graphene and single-walled carbon nanotube. (January 2017) - Kang, Jinhee; Atashin, Sanam; Jayaram, Shesha H.; Wen, John Z.
Abstract: Electrochemical double-layer capacitors, consisted of electrodes made of commercialized activated carbon (AC), graphene, and single-walled carbon nanotube (SWCNT) are fabricated and investigated, in order to reveal the dependency of their performance on charging/discharging frequency and operating temperature. Their electrochemical properties are quantified by means of cyclic voltammetry, constant current charge/discharge and electrochemical impedance spectroscopy. Through varying the applied frequency and operating temperature, correlations are identified between the capacitive and resistive behaviors of these electrodes and their representative porous structures including morphology, surface area, and pore size distribution (PSD). It is observed that the graphene and SWCNT electrodes, possessing larger meso-pores with a wide PSD, show better capacitive stabilities and shorter current response periods under high-frequency operations. They however exhibit a large variation of internal resistance over the operating temperature range of −30 °C to 60 °C. In contrast, the AC electrode, having a narrow PSD with mainly micro-pores, shows an increasing resistance and subsequently a longer current response period with increasing the applied frequencies. The dependency of its capacitance and resistance on temperature is found to be insignificant. A recently proposed equivalent circuit model is used to elucidate the activation energies of ion kinetics and diffusion processes in these electrodes. Highlights: Electrochemical properties of commercialized activated carbon, graphene, and singlewalled carbon nanotube are investigated Correlations are identified between capacitive and resistive behaviors and representative porous structures including morphology, surface area, and pore size distribution Meso-pores in graphene and SWCNT electrodes exhibit better capacitive stability with high-frequency operations and a large variation of resistance at −30 °C to 60 °C AC electrode with mainly micro-pores shows an increasing resistance with high frequencies and less dependency on operating temperatures